Bortezomib in combination with dose-adjusted EPOCH (etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin) induces long-term survival in patients with plasmablastic lymphoma: a retrospective analysis. Issue 9 (2nd September 2018) - Dittus, Christopher; Grover, Natalie; Ellsworth, Steven; Tan, Xianming; Park, Steven I.
Abstract: Plasmablastic lymphoma (PBL) is a rare and aggressive form of B-cell non-Hodgkin lymphoma. This subtype of lymphoma has a post-germinal center cell-of-origin called the plasmablast, and the immunophenotype is more consistent with that of a plasma cell than a lymphocyte. Because of these unique features, PBL is notoriously difficult to treat. Case reports and small reviews have evaluated the addition of agents directed against plasma cell disorders in combination with traditional lymphoma-directed regimens. We describe the largest case series to date, with the longest follow-up, evaluating bortezomib in combination with etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (V-EPOCH) for the treatment of PBL. Our results show that this is a safe and effective regimen with an overall and complete response rate of 100% and 2-year overall survival of 50%.